Screening of maize genotypes against southern leaf blight (Bipolaris maydis) during summer in Rampur, Chitwan, Nepal - Magar, P. B.; Khatri-Chhetri, G. B.; Shrestha, S. M.; Rijal, T. R. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was conducted during June to September, 2012, in the field at National Maize Research Program, Rampur, Chitwan, Nepal with the objective of screening 20 maize genotypes against southern leaf blight caused by Bipolaris maydis. Experiment was laid out in a randomized complete block design with three replications. Disease scoring was done as percentage of leaf area infected on individual plant at 7 days intervals starting from 50 days after sowing, for 6 times, and disease severity and mean AUDPC were calculated and yield recorded. Among the tested genotypes, there was variation in disease severity and mean AUDPC values. Disease severity was maximum on Yellow Popcorn (51.67%) and least on RML-32/RML-17 (7.27%). Based on mean AUDPC values, RML-32/RML-17 (20.53) appeared most resistant, followed by RML-4/NML-2 (23.66) and RML-4/RML-17 (25.90), while Yellow Popcorn (136.9) was found the most susceptible. Highest grain yield (4.90 t/ha) was also recorded on RML-32/RML-17 and least (2.49 t/ha) on Yellow Popcorn. Therefore the genotypes RML-32/RML-17, RML-4/NML-2 and RML-4/RML-17 could be used as the resistant varieties and source of resistance to southern leaf blight for varietal development of maize. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 115-122